Anxiety in Polish adult patients with inborn errors of immunity: a cross-sectional study - Grochowalska, Kinga; Ziętkiewicz, Marcin; Nowicka-Sauer, Katarzyna; Topolski, Mariusz; Więsik-Szewczyk, Ewa; Matyja-Bednarczyk, Aleksandra; Napiórkowska-Baran, Katarzyna; Zdrojewski, Zbigniew (Frontiers in Psychiatry, 2024)
Background: Patients with inborn errors of immunity (IEI) experience recurrent infections, autoimmunity, and malignancies. Owing to repeated medical procedures, the need for constant treatment and surveillance, and the unpredictable course of the disease, patients with IEI are prone to develop mental health disorders, including anxiety. In this study, we aimed to assess the prevalence and level of anxiety symptoms in adult Polish patients with IEI and explore the determinants of anxiety in this group of patients.Methods: Data from 105 Polish patients with IEI were collected via the hospital anxiety and depression scale (HADS), brief illness perception questionnaire (B-IPQ), illness cognition questionnaire (ICQ), Pittsburgh sleep quality index (PSQI), and a questionnaire on general health and demographic data. For statistical analyses of data, the normality of distribution of quantitative data was assessed, and internal consistency of tests was investigated using Cronbach's alpha coefficient; moreover, we performed the analysis of correlations and between-group differences, and path analysis to explore causal relationships. Significance was considered at p < 0.050. Results: Thirty-eight (36.2%) patients had anxiety symptoms (HADS-A ≥ 8); 14 (13.3%) patients had severe anxiety (score ≥ 11), and 24 (22.9%) had moderate anxiety (score of 8-10). Patients with poor sleep quality, higher pain frequency, younger age, and no fixed income had higher anxiety scores than others. Emotional and cognitive representations of illness were positively correlated with anxiety levels. Intense anxiety was related to more negative illness perception, higher helplessness, lower illness acceptance, and lower perceived benefits. Discussion: Anxiety is common in patients with IEI. However, results indicate that it is not related to a more severe course of IEI or several comorbidities, whereas, pain frequency and poor sleep quality were identified to be important clinical factors for anxiety. Because anxiety was related to negative illness perception, psychological therapy may apply to this group of patients.